Neural cognition processing of working memory in traumatic brain injury (TBI) patients - an ERP and a breamforming analysis of EEG and MEG data - Zahid, Aishah Sakinah (2019)
Traumatic Brain Injury is a type of brain damage that is caused by a jolt or blow to the head from blunt or penetrating trauma. It is a non-degenerative, non-congenital revile to the brain that leads to temporary or permanent deterioration of cognitive, physical, and psychosocial functions, with an associated diminished or altered state of consciousness. Neural oscillations are basic and important mechanism that enables the synchronization of neural activity across and within brain regions and stimulates the exact temporal coordination of neural processes underlying cognitive tasks such as cognition, memory, perception, and behaviour. The aim of this study is to investigate the changes of neural oscillations/brain oscillation during working memory task among Healthy and TBI participants, to investigate the changes the latency and amplitude of N170 and P300 component in working memory processing among Healthy and TBI participants and to localize the neural sources of working memory activity by using Beamforming analysis among Healthy and TBI participants. The method of this study is divided into three phases; 1) Recruitment phase; Where the participants are recruited based on inclusion and exclusion criteria, 2) Data collection; MEG and EEG recording and 3) Data Analysis; Neural oscillation (Delta, Theta, Alpha, Beta) and Amplitude and Latency of P300 and N170 analysis. The results are divided into 3 parts according to the objectives. 1) Changes in Neural Oscillation among TBI participants and Healthy participants: TBI participants showed significantly higher power of low-frequency wave (Delta and Theta) and higher power of High-frequency wave (Beta) activity compared to Healthy participants during the working memory task. 2) ERP component analysis of P300 and N170 Amplitude and Latency: Anomaly findings where TBI participants showed better results in term of Amplitude and Latency of P300 and N170. 3) The sources of P300 and N170 are located at the visual association area, sensory-motor and the area that is responsible for Working Memory processing. In conclusion, even the moderate TBI patients has shown rather greater attention to working memory task, the overall cognitive function processing of working memory was slightly deteriorated compared to their counterpart, the study will need to be replicated in a large sample of patients.